(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2016)
30 years ago on 10th February started the maxi trial, as it became known, against Cosa nostra. It is definitely one of the most important judicial event in the Italian history. For the first time in history the proposals contained in the Rognoni - La torre’s law were more extensively put into practice. The Review publishes a selection of excerpts of the injunction included the declarations of some informers such as Leonardo Vitale, Giuseppe Di Cristina, Tommaso Buscetta and Salvatore Contorno. The maxi trial ended on 30th January 1992 with the lifelong prison sentences for the so called “cupola” of Cosa nostra. Few months later Cosa nostra killed the two main injunction’s drafters.